ANALISIS PENGARUH PRODUCT QUALITY, PERCEIVED QUALITY, PERCEIVED VALUE DAN PROMOTION TERHADAP KEPUASAN PELANGGAN - , Nur Hidayat Dwi Santoso; , Dr. John Suprihanto, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this research study is to find out the most important factors that affect to customer satisfaction to the Kartu As customers. Which level of complaint increase during the price war in this hyper competition industry. This paper discusses the relationship between product quality, perceived quality, perceived value and promotion with customer satisfaction that involve 100 respondent from Kartu As with purposive sampling methods The study concluded that four independent variables have significant impact to customers satisfaction, that shows on multiple linear regression equation: CUS= 0.582 + 0.186PRQ + 0,146PEQ + 0,180PEV + 0.397PRO + error With level of explanation of independent variable to dependent variable achieve 74.7%.